Novel Lightweight Approach to Perform Cryptography for Data Security & Privacy in IoT Mobile Devices - Neve, Rahul; Bansode, Rajesh; Kaul , Vikas (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The lightweight cryptographic (LWC) algorithm is used for resource constraint devices. The performance analysis and development of LWC is for achieving better data security in resource constrained mobile devices for effective implementation. Literature survey on LWC was carried out where it was observed that the implementation of two well-known algorithms “SIMON” and “SPECK” are in latest research as per future technological requirements. On comparing SIMON & SPECK algorithms with conventional blocks, lightweight block ciphers the following challenges that are required to be mitigated by including usage of minimal hardware overhead in proposed design (e.g., time, memory consumption), viz. use of low-cost smart mobile devices, with minimal power, low energy consumption and improved security performance. Algorithms were implemented on the Raspberry Pi 3 with 1GB RAM, Quad Core 1.2GHz Broadcom BCM2837, with 32-bit Raspbian Operating System of 5V and current of 2 mA. Input to the algorithm is fed as text with varying size viz. 100kB, 200kB, 300kB, 400kB, 500kB.An attempt is made to developed hybrid LWC algorithm by using key scheduling logic of SPECK and Round function logic of SIMON. Experiment was performed using text file as inputs with varying sizes. On comparing the actual SIMON algorithm with Hybrid-SIMON_SPECKey algorithm it is observed that encryption and decryption time comsuption is 50% less. Thereby an improvement is observed in time and energy efficiency. Similarly in case of memory consumption of SPECK Algo with Hybrid SIMON-SPECKey algorithm it consumes an average 19% less memory during encryption as well as decryption.